Mental Distress and Its Contributing Factors Among Young People During the First Wave of COVID-19: A Belgian Survey Study - Rens, Eva; Smith, Pierre; Nicaise, Pablo; Lorant, Vincent; Van den Broeck, Kris (Frontiers in Psychiatry, 2021)
Background: The outbreak of the COVID-19 pandemic in 2020 and its associated measures led to high levels of mental distress in the general population. Previous research indicated that young people are especially vulnerable for a wide range of mental health problems during the pandemic, but little is known about the mechanisms. This study examined mental distress and its contributing factors among young Belgian people. Methods: An online survey was widely distributed in Belgium during the country’s lockdown and 16 to 25-year-olds were selected as a subsample. Mental distress was assessed using the 12-item General Health Questionnaire (GHQ-12), and a threshold of ≥ 4 was used to discriminate mental distress cases from non-cases. Bivariate and multivariate logistic regression analyses were performed to evaluate possible predictors of mental distress, including demographics, chronic condition, history of mental health problems, social support, exposure to COVID-19, and several changes in everyday activities. Results: A total of 2008 respondents were included, of which the majority was female (78.09%) and student (66.82%). The results indicate that about two thirds (65.49%) experienced mental distress. In the multivariate regression model, significant (p < .01) predictors of mental distress were female gender (OR = 1.78), low social support (OR = 2.17), loneliness (OR = 5.17), a small (OR = 1.63) or large (OR = 3.08) increase in social media use, a small (OR = 1.63) or large (OR = 2.17) decrease in going out for drinks or food, and a decrease in doing home activities (OR = 2.72). Conclusion: Young people experience high levels of mental distress during the COVID-19 pandemic. Our findings indicate that the mental distress was highest among women, those experiencing loneliness or low social support and those whose usual everyday life is most affected. The psychological needs of young people, such as the need for peer interaction, should be more recognized and supported.